عروض مختصرة - ملكاوي, أسماء حسين (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2011)
القرآن والمتغيرات الاجتماعية والتاريخية، محمد أبو القاسم حاج حمد، بيروت: دار الساقي للطباعة والنشر، 2011م، 141 صفحة. حوار حول: الإسلام هو القرآن وحده، محمد توفيق صدقي،رشيد رضا، طه البشري، جمع وتحقيق: هشام عبد العزيز، الرياض: جداول للطباعة والنشر والتوزيع، 2011م، 308 صفحة. نحو نظرية قرآنية، محمد سلمان غانم، بيروت: دار الفارابي، 2011م، 504 صفحة. الجدلية التاريخية في القرآن الكريم، عبد الله عيسى لحيلح، بيروت: منشورات زين الحقوقية، 2011م، 608 صفحة. الله والإنسان في القرآن: علم دلالة الرؤية القرآنية للعالم، توشيهيكو إيزوتسو، ترجمة وتقديم: هلال محمد الجهاد، لبنان: المنظمة العربية للترجمة، 2007م، 387 صفحة. الرحمانيةديموقراطية القرآن، محمد سلمان غانم، بيروت: دار الفارابي، 2008م، 246 صفحة. الانتماء الحضاري والهوية الثقافية في ضوء عروبة القرآن أو الإسلام العربي، معالم في طريق الوحدة والتعايش والاعتدال لتدبّر القرآن وفهمه بلسان عربي مبين، علاء الدين المدرس، العراق: دار الرقيم، 2008م، 191 صفحة. The Impact of the Qur'anic Verses on Mass Communication Practices: A Case Study, Aliy Abdulwahid Adebisi, Germany- LAP LAMBERT Academic Publishing, 2011, 72 pages. The Dream in Islam: From Qur'anic Tradition to Jihadist Inspiration, Iain R. Edgar, Berghahn Books, 2011, 172 pages. Qur'anic Hermeneutics: Al-Tabrisi and the Craft of Commentary (Routledge Studies in the Qur'an), Bruce Fudge, UK- Routledge; 1 edition, 2011, 176 pages. Communication Strategies in the Qur'an: A Multidisciplinary Approach, Christian Tamas, Germany- LAP LAMBERT Academic Publishing, 2011, 252 pages. Al-Ghazali and the Qur'an: One Book, Many Meanings (Culture and Civilization in the Middle East), Martin Whittingham, UK- Routledge; Reprint edition, 2011, 154 pages. Beyond The Quran, Responding to Islam’s Claim on Bible Prophecies. James Paul-Magidi, Longwood, FL- Xulon Press, 2011, 464 pages. In Search of Our Origins: How the Quran Can Help in Scientific Research, Jamshed Akhtar, Seattle, WA- CreateSpace, 2010, 164 pagesز Sounds of Qur'anic Recitation in Egypt: A Phonetic Analysis, Mohammed R. Elashiry See search results for this auAre you an author? Learn about Author Central (Author), Bruce Ingham (Foreword), New York- Edwin Mellen Pr, 2009, 352 pages. Textual Criticism and Qur'an Manuscripts, Keith E. Small, Lanham, MD.: Lexington Books, 2011, 244 pages. Life, The Universe & The Quran, Dr Saddique, Bloomington, IN.: AuthorHouse, 2011, 156 pages. Women, War & Hypocrites: Studying the Qur'an, Robert A Campbell, Sydney: Cape Breton University Press, 2010, 244 pages. للحصول على كامل المقالة مجانا يرجى النّقر على ملف ال PDF في اعلى يمين الصفحة.